CUPS, COSTS, AND CLICKS AS DRIVERS OF COFFEE SHOP LOYALTY IN PALEMBANG - Catharina Clara; Fifi Angelita (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2025)
Customer loyalty has become difficult to maintain for independent coffee shops in Palembang due to increasing competition and changing consumer preferences. This study aims to examine how service quality, price perception, and social media marketing relate to customer loyalty, with customer satisfaction and brand image considered as mediating variables. The study collected data from 130 coffee shop customers in Palembang using purposive sampling. Data were gathered through a structured questionnaire adapted from previous studies and analyzed using Structural Equation Modeling with SmartPLS. The results show that customer satisfaction has a central role in shaping customer loyalty. Service quality and social media marketing do not directly influence loyalty but show stronger effects when they improve customer satisfaction. Brand image also affects loyalty, especially in relation to price perception. These findings indicate that customer loyalty is formed through consistent value delivery and positive consumption experiences rather than short term promotional activities. For coffee shop owners, the results suggest the need to maintain service performance, offer fair pricing, and engage customers consistently to support satisfaction and loyalty in a competitive market.